Long-term outcomes of less drug-eluting stents by the use of drug-coated balloons in de novo coronary chronic total occlusion intervention: A multicenter observational study - Wang, Xi; Yang, Xinyue; Lu, Wenjie; Pan, Liang; Han, Zhanying; Pan, Sancong; Shan, Yingguang; Wang, Xule; Zheng, Xiaolin; Li, Ran; Zhu, Yongjian; Qin, Peng; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Data on drug-coated balloons (DCB) for de novo coronary chronic total occlusion (CTO) are limited. We aimed to investigate the long-term outcomes of substitution of drug-eluting stents (DES) by DCB. Methods We compared the outcomes of less DES strategy (DCB alone or combined with DES) and DES-only strategy in treating de novo coronary CTO in this prospective, observational, multicenter study. The primary endpoints were major adverse cardiovascular events (MACE), target vessel revascularization, myocardial infarction, and death during 3-year follow-up. The secondary endpoints were late lumen loss (LLL) and restenosis until 1-year after operation. Results Of the 591 eligible patients consecutively enrolled between January 2015 and December 2019, 281 (290 lesions) were treated with DCB (DCB-only or combined with DES) and 310 (319 lesions) with DES only. In the DCB group, 147 (50.7%) lesions were treated using DCB-only, and the bailout stenting rate was relatively low (3.1%). The average stent length per lesion in the DCB group was significantly shorter compared with the DES-only group (21.5 ± 25.5 mm vs. 54.5 ± 26.0 mm, p < 0.001). A total of 112 patients in the DCB group and 71 patients in the DES-only group (38.6% vs. 22.3%, p < 0.001) completed angiographic follow-up until 1-year, and LLL was much less in the DCB group (−0.08 ± 0.65 mm vs. 0.35 ± 0.62 mm, p < 0.001). There were no significant differences in restenosis occurrence between the two groups (20.5% vs. 19.7%, p > 0.999). The Kaplan–Meier estimates of MACE at 3-year (11.8% vs. 12.0%, log-rank p = 0.688) was similar between the groups. Conclusion Percutaneous coronary intervention with DCB is a potential “stent-less” therapy for de novo CTO lesions with satisfactory long-term clinical results compared to the DES-only approach.